Assessing the Persistence and Mobility of Organic Substances to Protect Freshwater Resources - Arp, Hans Peter H.; Hale, Sarah E. (ACS Environmental Au, 2022)
Persistent and mobile organic substances are those with the highest propensity to be widely distributed in groundwater and thereby, when emitted at low-levels, to contaminate drinking water extraction points and freshwater environments. To prevent such contamination, the European Commission is in the process of introducing new hazard classes for persistent, mobile, and toxic (PMT) and very persistent and very mobile (vPvM) substances within its key chemical regulations CLP and REACH. The assessment of persistence in these regulations will likely be based on simulated half-life, t 1/2, thresholds; the assessment of mobility will likely be based on organic carbon–water distribution coefficient, K OC, thresholds. This study reviews the use of t 1/2 and K OC to describe persistence and mobility, considering the theory, history, suitability, data limitations, estimation methods, and alternative parameters. For this purpose, t 1/2, K OC, and alternative parameters were compiled for substances registered under REACH, known transformation products, and substances detected in wastewater treatment plant effluent, surface water, bank filtrate, groundwater, raw water, and drinking water. Experimental t 1/2 values were rare and only available for 2.2% of the 14 203 unique chemicals identified. K OC data were only available for a fifth of the substances. Therefore, the usage of alternative screening parameters was investigated to predict t 1/2 and K OC values, to assist weight-of-evidence based PMT/vPvM hazard assessments. Even when considering screening parameters, for 41% of substances, PMT/vPvM assessments could not be made due to data gaps; for 23% of substances, PMT/vPvM assessments were ambiguous. Further effort is needed to close these substantial data gaps. However, when data is available, the use of t 1/2 and K OC is considered fit-for-purpose for defining PMT/vPvM thresholds. Using currently discussed threshold values, between 1.9 and 2.6% of REACH registered substances were identified as PMT/vPvM. Among the REACH registered substances detected in drinking water sources, 24–30% were PMT/vPvM substances.